Noninvasive identification of human central sulcus: a comparison of gyral morphology, functional MRI, dipole localization, and direct cortical mapping - Towle, Vernon L; Khorasani, Leila; Uftring, Stephen; Pelizzari, Charles; Erickson, Robert K; Spire, Jean-Paul; Hoffmann, Kenneth; Chu, David; Scherg, Michael (NeuroImage (Orlando, Fla.), 2003)
The locations of the human primary hand cortical somatosensory and motor areas were estimated using structural and functional MRI, scalp-recorded somatosensory-evoked potential dipole localization, expert judgments based on cortical anatomy, and direct cortical stimulation and recording studies. The within-subject reliability of localization (across 3 separate days) was studied for eight normal subjects. Intraoperative validation was obtained from five neurosurgical patients. The mean discrepancy between the different noninvasive functional imaging methods ranged from 6 to 26 mm. Quantitative comparison of the noninvasive methods with direct intraoperative stimulation and recording studies did not reveal a significant mean difference in accuracy. However, the expert judgments of the location of the sensory hand areas were significantly more variable (maximum error, 39 mm) than the dipole or functional MRI techniques. It is concluded that because expert judgments are less reliable for identifying the cortical hand area, consideration of the findings of noninvasive functional MRI and dipole localization studies is desirable for preoperative surgical planning.